Speech By Brig. Jen. Dato’ Prof. Dr. Kamarudin Hussin Vice Chancellor of UniMAP IEC Orientation Week - Kamarudin, Hussin, Brig. Jen. Dato’ Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
IEC Orientation Week was held on 18 October 2011.